SPECIAL CONCRETE AND COMPOSITES 2018 : 15th international conference - Editorial, Foreword (Acta Polytechnica CTU Proceedings, 2019)
Thanks to modern technology and demanding applications is an area of special concrete very rapidly growing field. Among the special concretes are such types of concrete that is something markedly different from the traditional concrete. This is not necessarily only difference in the final properties, but e.g. in the method of manufacture or use. These types of concrete have been specifically developed to advance and expand the possibility of cement composites utilization. The contributions present the latest findings from the development and application of special composites in construction. Attention is paid to the fields of concrete use in demanding environment, applications of HPC and to sustainable development issues. Generally, currently large attention is paid to the energy efficiency of human activities, including construction, and to their impact on environment. In this context, the environmental issues are often taken into account in the design of buildings, including the building materials. In the research and development of special concretes is this new direction expressed also by studying supplementary cementitious materials. However, the issue of sustainability of construction and systematic improvement of energy efficiency of buildings is very complex problem that will continue to be subject of further research. Date: October 11.-12., 2018 Venue: Skalský Dvůr, Czech Republic URL: http://www.sekurkon.cz/kurz/10105 Organised by: Sekurkon s.r.o. Experimental Centre, Faculty of Civil Engineering, Czech Technical University in Prague Guest editor: Pavel Reiterman Scientific comittee: Petr Konvalinka Lenka Bodnárová Petr Huňka Tomáš Klečka Karel Kolář Jiří Litoš Pavel Reiterman Jan Vodička Local organizing comittee: Helena Šubrtová Pavel Reiterman Guarantor of the peer review process: Pavel Reiterman Guarantor of language editing: Pavel Reiterman